Y‐chromosome and mtDNA variation confirms independent domestications and directional hybridization in South American camelids. (11th July 2017) - Marín, J. C.; Romero, K.; Rivera, R.; Johnson, W. E.; González, B. A.
Summary: Investigations of genetic diversity and domestication in South American camelids (SAC) have relied on autosomal microsatellite and maternally‐inherited mitochondrial data. We present the first integrated analysis of domestic and wild SAC combining male and female sex‐specific markers (male specific Y‐chromosome and female‐specific mtDNA sequence variation) to assess: (i) hypotheses about the origin of domestic camelids, (ii) directionality of introgression among domestic and/or wild taxa as evidence of hybridization and (iii) currently recognized subspecies patterns. Three male‐specific Y‐chromosome markers and control region sequences of mitochondrial DNA are studied here. Although no sequence variation was found in SRY and ZFY, there were seven variable sites in DBY generating five haplotypes on the Y‐chromosome. The haplotype network showed clear separation between haplogroups of guanaco–llama and vicuña–alpaca, indicating two genetically distinct patrilineages with near absence of shared haplotypes between guanacos and vicuñas. Although we document some examples of directional hybridization, the patterns strongly support the hypothesis that llama ( Lama glama ) is derived from guanaco ( Lama guanicoe ) and the alpaca ( Vicugna pacos ) from vicuña ( Vicugna vicugna ). Within male guanacos we identified a haplogroup formed by three haplotypes with different geographical distributions, the northernmost of which (Peru and northern Chile) was also observed in llamas, supporting the commonly held hypothesis that llamas were domesticated from the northernmost populations of guanacos ( L. g. cacilensis ). Southern guanacos shared the other two haplotypes. A second haplogroup, consisting of two haplotypes, was mostly present in vicuñas and alpacas. However, Y‐chromosome variation did not distinguish the two subspecies of vicuñas.